Synaesthesia - Michael Banissy (Frontiers Research Topics, 2015)
Synaesthesia is a rare experience in which one property of a stimulus evokes a secondary experience that is not typically associated with the first (e.g. hearing words can evoke tastes). In recent years a number of studies have highlighted the authenticity of synaesthesia and attempted to use the experience to inform us about typical processes in perception and cognition. This Research Topic brings together research on synaesthesia and typical cross modal interactions to discuss the mechanisms of synaesthesia and what it can tell us about typical perceptual processes. Topics include, but are not limited to, the neurocognitive mechanisms that give rise to synaesthesia; the extent to which synaesthesia does / does not share commonalities with typical cross-modal correspondences; broader cognitive and perceptual consequences that are linked to synaesthesia; and perspectives on the origins / defining characteristics of synaesthesia.